Cytotoxic compounds from Wrightia pubescens (R.Br.) - De Los Reyes, Mariquit (Animo Repository, 2018)
Background: Mixtures of ursolic acid (1) and oleanolic acid (2) (1:1 and 1:2), oleanolic acid (2), squalene (3), chlorophyll a (4), wrightiadione (5), and μ-amyrin acetate (6) were isolated from the dichloromethane (CH2Cl2) extracts of the leaves and twigs of Wrightia pubescens (R.Br.). Objectives: To test for the cytotoxicity potentials of 1-6. Materials and Methods: The antiproliferative activities of 1-6 against three human cancer cell lines, breast (MCF-7) and colon (HT-29 and HCT-116), and a normal cell line, human dermal fibroblast neonatal (HDFn), were evaluated using the PrestoBlue® cell viability assay. Results: Compounds 4, 1 and 2 (1:2), 2, 1 and 2 (1:1), and 5 exhibited the most cytotoxic effects against HT-29 with half maximal inhibitory concentration (IC50) values of 0.68, 0.74, 0.89, 1.70, and 4.07 μg/mL, respectively. Comparing 2 with its 1:1 mixture with 1 (IC50=1.70 and 7.18 μg/mL for HT-29 and HCT-116, respectively) and 1:2 mixture with 1 (0.74 and 3.46 μg/mL for HT-29 and HCT-116, respectively), 2 also showed strong cytotoxic potential against HT-29 and HCT-116 (0.89 and 2.33 μg/mL, respectively). Unlike the mixtures which exhibited low effects on MCF-7 (IC50=20.75 and 30.06 μg/mL for 1:1 and 1:2, respectively), 2 showed moderate activity against MCF-7 (10.99 μg/mL). Compound 6 showed the highest cytotoxicity against HCT-116 (IC50=4.07 μg/mL). Conclusion: Mixtures of 1 and 2 (1:1 and 1:2), 2, 3, 4, 5, and 6 from the CH2Cl2extracts of the leaves and twigs of W. pubescens (R.Br.) exhibited varying cytotoxic activities. All the compounds except 6 exhibited the strongest cytotoxic effects against HT-29. On the other hand, 6 was most cytotoxic against HCT-116. Overall, the toxicities of 1-6 were highest against HT-29, followed by HCT-116 and MCF-7. All the compounds showed varying activities against HDFn (IC50< 30 μg/mL). Abbreviation Used: IC50: Half maximal inhibitory concentration.